Spider toxins activate the capsaicin receptor to produce inflammatory pain - Siemens, Jan; Zhou, Sharleen; Piskorowski, Rebecca; Nikai, Tetsuro; Lumpkin, Ellen A.; Basbaum, Allan I.; King, David; Julius, David (Nature, 2006)
Three peptides isolated from the venom of the West Indian tarantula Psalmopoeus cambridgei have been found to promote pain and inflammation by activating the same neuronal receptor as capsaicin, the hot component of chilli peppers. This suggests that tarantulas and chillis use similar tactics to deter predators. The newly discovered peptides are also unusual because they trigger an excitatory response. Peptides with similar structures that bind to other ion channels are already known, but are inhibitory.